Pendekatan STEM dalam Meningkatkan Kemampuan Berpikir Kreatif Matematis: Pendekatan STEM dalam Meningkatkan Kemampuan Berpikir Kreatif Matematis - Syarifah Ayu (Program Studi Pendidikan Matematika jenjang Magister, FMIPA, Universitas Negeri Jakarta, 2025)
Creative thinking ability is very important for every individual and is an essential skill needed in the 21st century. However, the reality found based on the results of PISA and TIMSS shows that the creative thinking ability of Indonesian students is relatively low. One approach that can improve students' mathematical creative thinking skills is STEM (Science, Technology, Engineering, and Mathematics). This study aims to describe the STEM approach and the implementation of STEM in improving students' mathematical creative thinking skills. The research method used is literature review. The articles used were 23 articles closely related to the keywords and selection criteria obtained from Google Scholar, ResearchGate, Semantic Scholar with the help of the Publish or Perish application. Based on the literature review that has been presented, the STEM approach is proven to improve students' mathematical creative thinking skills. STEM implementation can be integrated with Problem Based Learning (PBL), Project Based Learning (PjBL), and inquiry learning models.